Vortex rectification and phase slips in superconducting granular aluminum - Maughan, Weston F., II, author; Field, Stuart B., advisor; Gelfand, Martin, committee member; Buchanan, Kristen, committee member; Neilson, James R., committee member (Colorado State University. Libraries, 2020)
Superconductivity is a unique and interesting phenomenon that manifests as a new phase of matter in a wide variety of materials. The most well-known property of superconductors is that they exhibit perfect conductivity when cooled below a critical temperature Tc. In addition to their perfect conductivity, superconductors exhibit the equally fundamental Meissner effect that expels magnetic fields from the interior of the material. While applications of a material that exhibits perfect conductivity, such as generating large magnetic fields via electromagnets or transmitting a large current with zero dissipation, are highly desired, the subtle details of flux penetration into mesoscopic samples may also be exploited to realize useful devices, or as a testbed to understand one-dimensional superconductivity. In this work, the nature of superconductivity in granular aluminum was explored in two mesoscopic sample classes: first, by studying Abrikosov vortices in films, and then by studying dissipation from phase slips in one-dimensional nanowires. The penetration of an applied field is possible in film sample geometries, even though the Meissner effect generally expels flux. This penetration occurs in type-II superconductors via quantized flux bundles through normal regions or domains of the superconductor called vortices. The behavior and dynamics of these vortices are of significant interest as they can be exploited to realize fluxonic devices that perform circuit operations analogous to the operations performed with electrons in electronics. One method to influence the motion of vortices within a superconductor in order to realize a fluxonic device is to introduce a periodic potential landscape that causes an easy and a hard direction for vortex motion. In other words, the vortex motion is rectified. By realizing a so-called vortex ratchet with such a potential landscape, vortices may easily be introduced or removed from the superconductor by driving them in the easy or hard directions respectively. We begin by studying the rectification properties of both symmetrically and asymmetrically thickness-modulated superconducting films. These thickness modulations were fabricated with an elegant method of angle-sputter deposition of granular aluminum onto a glass substrate that has a sinusoidal modulation in its thickness. We then explored the rectification of these symmetric and asymmetric films by studying the motion of vortices using cryogenic transport measurements. In these measurements, vortices are driven in both directions across a modulated sample and the resulting voltages are measured. Differences in the voltages corresponding to motion in opposite directions imply that the vortices move more readily in one direction, that is, that there is an overall rectification in their motion. While these measurements performed with the symmetric washboard film seemed to exhibit reversibility in the transport properties, the asymmetric washboard exhibited a mild asymmetry that was much smaller than expected. This result indicates that the potential landscape is influenced by another source in addition to the asymmetric thickness modulation. To better understand these effects, we tested the influence of the sample edges on the nucleation of vortices with two multi-segment films. These multi-segment films were fabricated in either an 8- or 14-probe geometry where each segment shares a vertical reference edge, while the opposing edges between pairs of voltage leads contain tapers of varying lengths which were fabricated lithographically. Clear rectification effects are observed with cryogenic transport measurements of these samples, with enhanced rectification for longer taper lengths showing the importance of the sample edge geometry on vortex motion. Following these studies in superconducting films, we explored the nature of dissipation in one-dimensional superconducting nanowires. Recent advancements in laboratory fabrication techniques have reduced the accessible size scale of superconducting samples into the nanometer regime. As a result, superconductors can be fabricated that exhibit one-dimensional superconductivity, in which the complex superconducting order parameter ψ is restricted to fluctuations along the length of the nanowire because its cross-sectional dimensions are smaller than ξ. Experiments performed with these nanowires exhibit a non-zero resistance even when the samples were cooled below Tc. This dissipation is understood as due to thermal fluctuations that cause |ψ| to vanish in a small segment of the wire of length ∼ξ, allowing the superconducting phase to "slip" by ±2π, resulting in a voltage pulse. However, several experimental studies have observed excess nanowire resistance at low temperatures that cannot be described with this thermal fluctuation model alone. Some researchers have proposed that macroscopic quantum tunneling events lead to the excess resistance, while other studies claim that nanowire inhomogeneities influence the thermally activated phase slip rate. In order to provide insight into the origin of the excess nanowire resistance, we performed cryogenic scanning experiments to map the local phase-slip rate along a superconducting nanowire. This was achieved by scanning either a dielectric or a magnetic tip with a home- built cryogenic atomic force microscope (cryo-AFM) to locally perturb superconductivity along a granular aluminum nanowire, while simultaneously measuring the nanowire resistance. This required the construction and characterization of the cryo-AFM along with a method of locating nanowire samples at cryogenic temperatures. We then fabricated one-dimensional granular aluminum nanowires with electron beam lithographic (EBL) techniques. We scanned these nanowires with the cryo-AFM and found that a dielectric tip does not locally perturb superconductivity enough to cause a measurable change in the wire resistance. However, repeating this experiment with either a magnetic tip or another material may plausibly elucidate the origins of the low-temperature nanowire dissipation.
Keywords: granular aluminum; superconductivity; phase slip; Abrikosov vortex